A blockchain searchable encryption scheme for legal data shared by multiple parties - Zemin Wang (Journal of Applied Science and Engineering)
The national judicial system has put forward higher requirements for the sharing of legal data, but existing legal data sharing schemes still have some problems, such as weak data security, unrestricted user access. They are difficult to meet the specific needs of shared data. In order to solve these problems, a blockchain searchable encryption scheme that can realize multi-party sharing of legal data is proposed. The combination of conditional broadcast agent re-encryption and public key searchable encryption protects the confidentiality of legal data and realizes the keyword trapdoor search. The proxy re-encryption is added to the broadcast mechanism to realize the multi-user sharing of encryption once, reduce the computing burden of the data owner, and achieve fine-grained access control through conditional value setting. The multi-party search and sharing model of encrypted legal data is designed, and the keyword file number is stored and indexed by the blockchain, so as to ensure that the data cannot be tampered with and the search is reliable. The analysis results show that the scheme realizes the safe search and sharing of legal data, and the multi-user controllable sharing is suitable for the new judicial system with complex data exchange.